Nilai Budaya dan Pendidikan: Revitalisasi, Dekonstruksi dan Rekonstruksi - Ali Rohmad (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2015)
Fundamental social change in an era of globalization that tends to establish communication between the population of the world without any barriers of a country's territorial boundaries resulted in the acceleration of the shift cultural values also result in the acceleration of the shifting role of education within the scope of the informal and formal and non-formal. To face the reality of this change, the author of a scientific journal article recommends three kinds of alternatives role of education in passing cultural values to the next generation successor to current and future generations.